50 lat warsztatów muzycznych w Chodzieży. Wspomnienia uczestników = 50 years of music workshops in Chodzież. The memories of participants - Szrom, Janusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The Jazz Workshops "Cho-Jazz" in Chodzież earned extraordinary reputation in the musical environment for years. Organized since 1971 as the first summer jazz school in Europe, today it is most likely the only such cultural event in the world, which has been continuously educating young jazz adepts for over 50 years.
Keywords: jazz; jazz workshop; Chodzież; Cho-Jazz